Characterization of the Saxitoxin Biosynthetic Starting Gene, sxta in the Toxic Dinoflagellate Alexandrium tamiyavanichii - Kieng, Soon Hii; Po, Teen Lim; Toh, Hii Tan; Chui, Pin Leaw (Universiti Malaysia Sarawak (UNIMAS), 2012)
Recently, molecular genetics of the Saxitoxin (STX) biosynthesis pathway has become one of the major focuses in paralytic shellfish poisoning (PSP) toxin-related studies after the recent discovery of STX biosynthetic genes in toxic cyanobacteria and later in the toxic dinoflagellates. Here we described the two domains of sxtA, SAM-dependent methyltransferase coding gene, sxtA1 and the class II aminotransferase coding gene, sxtA4 from a toxic strain of Alexandrium tamiyavanichii isolated from Samariang, Sarawak.